Determination of crop evapotranspiration and partitioning of bare soil evaporation of mustard using weighing type field lysimeters - GUPTA, A.; SARANGI, A.; SINGH, D. K. (Journal of Soil and Water Conservation, 2020)
Determination of crop evapotranspiration (ETc) plays a significant role in estimating crop water requirement and subsequently irrigation scheduling of different crops leading to saving of water. Keeping this in view, the research work was undertaken to determine crop evapotranspiration (ETc)of mustard (Brassica juncea) cultivar Pusa Vijay (NPJ-93) and bare soil evaporation (E) using weighing type field lysimeters located at the research farm of Water Technology Centre, ICAR-IARI, New Delhi, India during rabi seasons of 2013-14 and 2014-15. It was observed that the average value of ETc during rabi 2013-14 season was 155.3 mm. Whereas, during rabi 2014-15 season, the value of ETc was 151.8 mm. Mean values of daily ETc were 1.23 mm/day and 1.08 mm/day during rabi seasons of 2013-14 and 2014-15, respectively.Mean monthly crop coefficient (Kc) values were estimated and relationship between Kc and Leaf Area Index (LAI) was established. The ratio of transpiration (T) to ETc was 0.70 during both the years. Nonetheless, the estimated ETc values of mustard and E can be used for judicious irrigation scheduling.